Cyprus : Staff Report for the 2006 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2006 Article IV Consultation highlights that economic activity in Cyprus has recovered from a relatively weak performance in 2002-03. Declines in interest rates and strong capital inflows associated with Cyprus's accession to the European Union in May 2004 spurred growth in private consumption and investment while recovering tourist receipts reduced the external drag on the economy. The economy is experiencing rapid credit growth and brisk housing price increases. Total credit to the private sector accelerated recently, with mortgage lending leading the expansion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet